Analysis of factors related to the incidence of hypertension in the elderly - Menis Mbali; Sriyana Herman; Abdul Rahman (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2024)
Introduction: Hypertension or high blood pressure is one of the main health problems in the elderly population in various parts of the world. The elderly are more susceptible to hypertension due to the aging process that affects the elasticity of blood vessels, as well as increased peripheral resistance. In addition, various risk factors, such as an unhealthy lifestyle, poor diet, and certain medical conditions, can worsen the condition of hypertension in the elderly. Objective: This study aims to analyze factors related to the incidence of hypertension in the elderly. Methods: This research uses a cross-sectional design, an analytical study that studies the causes of incidents or incidents. Data collection uses a questionnaire. The sample in this study was 64 elderly hypertensive patients in the working—data analysis using the chi-square test. Result: The results of this study indicate that there is a relationship between physical activity (p=0.000), obesity (p=0.000), diet (p= 0.029), smoking habits (p=0.000), and work (p=0.020) with the incidence of hypertension in the elderly in working. Conclusion: The incidence of hypertension in the elderly with the variables studied shows that there is a relationship, and the most related variable is obesity. So, it is hoped that the elderly, especially those who are obese, should be given intervention to maintain their diet so that complications do not occur and can reduce the risk of hypertension.